Chinese materia medica used in medicinal diets. (12th July 2017) - Tan, Fang; Chen, Yalin; Tan, Xiaolei; Ma, Yunyun; Peng, Yong
Abstract: Ethnopharmacological relevance: Medicinal diets have a history of more than 2000 years. Locally referred to as yaoshan (Chinese: 药膳), a medicinal diet is understood in China as a dietary product that combines herbs and food with the purpose of preventing and treating diseases or improving health under the guidance of traditional Chinese medicine theory. Medicinal diets are used in Chinese people's daily life and in specialized restaurants. Hundreds of Chinese materia medica (CMM) are used in medicinal diets; however, a comprehensive evaluation of medicinal diets is lacking. Aims of the study: This is an exploratory study that aims to identify the CMM that are most frequently used in medicinal diets and to provide an updated view of the current situation of medicinal diets in China. Materials and methods : A field study of 1221 people in 32 Chinese provinces was conducted over a period of approximately 6 months and included various types of interviews as well as a written questionnaire. Two approaches were used to analyse the data collected in the survey: (1) estimating the frequency of CMM consumed in daily diets; and (2) collecting CMM used in medicinal diet restaurants. Complementary information on the selected CMM was obtained from relevant databases, including PubMed, Google Scholar, Baidu Scholar, CNKI, and Web of Science. Results : Ten CMM were reported as commonly used by more than 50% of the participants. Among these 10 species, most medicinally used parts were seeds and fruits. Pharmacological data from the literature revealed that these species are associated with a wide spectrum of biological properties, including antitumour (80%), antioxidant (50%), anti-diabetic (40%), antilipemic (40%), anti-aging (40%), antimicrobial (40%) and cardioprotective (40%) activities. Our survey shows that most medicinal diet restaurants are located in the eastern part of China, with the greatest numbers being found in Beijing and Guangzhou. Only Dioscoreae Rhizoma, Lycii Fructus, Chrysanthemi Flos and Longan Arillus were frequently consumed both in daily diets and at medicinal diet restaurants. Some of the similarities shared by these 4 species include an extensive history of use (>2000 years); a sweet flavour; and antioxidant, antidiabetic, antilipemic and cardioprotective effects. Conclusions: The 10 most commonly consumed CMM possess various biological effects that are currently target the most frequent health problems for the majority of the population. The development of medicinal diet restaurants has certain regional restrictions and is associated with the local climate environment and dietary culture. The data revealed by this study provided useful information for commercial exploitation of medicinal diets and their components and serve as a basis for further studies on various aspects of medicinal diets. Graphical abstract: